2015
DOI: 10.1016/j.jvs.2014.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovenous anastomosis for recurrent swelling syndrome and chylous effusion due to cervical thoracic duct cyst

Abstract: Thoracic duct (TD) cyst is an uncommon abnormality that can be manifested as a cervical swelling. Pathogenesis includes congenital or degenerative weakness of the wall of the TD and obstruction of the lymphoid flow. Diagnosis is crucial to eliminate malignant disease or vein thrombosis and can be established by imaging and needle aspiration. We report a case of recurrent cervical swelling with spontaneous chylothorax and chyloperitoneum. A TD cyst with a terminal obstruction of the TD was diagnosed on lymphang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 14 publications
(14 reference statements)
0
45
0
Order By: Relevance
“…Reported investigations include angiocardiography, FNA for cytology and biochemical testing, ultrasonography, open biopsy, colour-coded Doppler, lymphoangiography (also known as lymphography), cystography (direct puncture of contrast media to cyst), lymphoscintigraphy, CT, MRI, and PET scan. Lymphangiography is considered as the ‘gold standard’ imaging tool by many authors as this delineates the mediastinal and cervical segments of the thoracic duct up to the inlet to the junction of the left subclavian vein and internal jugular vein [4-7]. It can also be combined with aspiration techniques.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reported investigations include angiocardiography, FNA for cytology and biochemical testing, ultrasonography, open biopsy, colour-coded Doppler, lymphoangiography (also known as lymphography), cystography (direct puncture of contrast media to cyst), lymphoscintigraphy, CT, MRI, and PET scan. Lymphangiography is considered as the ‘gold standard’ imaging tool by many authors as this delineates the mediastinal and cervical segments of the thoracic duct up to the inlet to the junction of the left subclavian vein and internal jugular vein [4-7]. It can also be combined with aspiration techniques.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The cause of CTDC is unclear. Several aetiologies have been proposed including congenital weakness [11-13], distal obstruction of the duct [14, 15], degeneration of cervical thoracic duct wall from inflammation or atherosclerotic changes [4, 7, 16], and neck trauma which could be iatrogenic [17] or secondary to blunt injury like whiplash [18-20]. Our literature review reported that the possible pathogenesis are distal obstruction (16/47; 34%), wall degeneration (7/47; 15%), trauma (5/47; 11%), congenital wall weakness (4/47; 9%), and a third had unknown cause or not elaborated in the full report (16/47; 34%).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations